Rivaroxaban versus low-molecular-weight heparins for short- and long-term prognosis in patients with deep vein thrombosis after spontaneous intracranial hemorrhage - Jingfan Li; Qi Song; Guannan Tong; Chengyu Bian; Huimei Zhang; Hulin Zheng; Yafei Wang (Journal of Comparative Effectiveness Research)
Aim: Anticoagulation is the cornerstone of deep vein thrombosis (DVT) treatment, but in patients with intracerebral hemorrhage, it requires a delicate balance between preventing thrombosis and minimizing the risk of rebleeding. To assess the effects of rivaroxaban on short- and long-term clinical prognosis in patients with DVT who have suffered spontaneous intracranial hemorrhage (sICH). Materials & methods: The study retrospectively enrolled 327 sICH patients with DVT from 11 October 2019 to 18 September 2023. The primary outcomes were defined as recurrent sICH, bleeding-related events and mortality within 90 days and 1 year. Multivariate logistic regression was conducted to evaluate the association between rivaroxaban and clinical outcomes based on inverse probability of treatment weighting. Results: Of the included patients, 230 received low-molecular-weight heparins (LMWH) and 97 received rivaroxaban. The reoccurrence rate of sICH was 1.30 and 2.06% in the LMWH and rivaroxaban groups, respectively. Bleeding rates were 8.70% in the LMWHgroup and 5.15% in the rivaroxaban group. The mortality was less frequent in patients received rivaroxaban than LMWH, following up 90 days (8.25 vs 15.65%, p = 0.07) and 1 year (10.42 vs 25.22%, p = 0.003). Multivariate and inverse probability of treatment weighting-adjusted analyses confirmed the association of rivaroxaban with reduced 1-year mortality and better functional recovery. Conclusion: Rivaroxaban use in DVT patients after sICH was associated with lower long-term mortality and better functional independence, without significantly increasing the risk of sICH recurrence or bleeding complications. These findings should be interpreted with caution and require confirmation through prospective randomized trials.